Mobile Learning and Immutable Mobiles: Using iPhones to support informal learning in craft breweries - Wright, Steven; Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2012)
How are mobile devices used to support learning in informal settings? The majority of m-learning research to date has focussed on formal or professional learning contexts and is marked by controlling the devices used and the tasks to be completed. Studying learning and practice in an informal context provides an insight into how mobile devices are used when the device, applications, and practices are determined by the participant rather than a research agenda. In this observational study we draw on multi-site and focussed ethnographic approaches to trace the connections between practices, calculation, evaluation, a learning community and the central role of an iPhone in forming these connections in two craft breweries. An actor-network theory (ANT) sensibility provides the vocabulary and focus for a consideration of the agency of the heterogeneous actants in the breweries. We use ANT to consider not only the human and non-human actants observed, but also the processes of calculation and qualitative evaluation which are brought together in the concept of ‘qualculation’. We introduce the challenge of ANT to conventional notions of the process of learning, drawing on the work of Steve Fox (2001), and note the limits of this work in setting out the challenge but not what would show evidence of learning in an actor-network. We trace how a recipe is transformed from originating beer through both physical and calculated transformations and show the role of the iPhone in achieving these in two breweries. A novice brewery expends significant effort in attempting to maintain the immutability of the recipe and to conform to its predicted outcomes. We consider in detail moments of breakdown and mistranslation and show how the recipe remains mobile but immutable while the brewery itself becomes the location of change and development. An experienced brewery transforms and changes the recipe with the help of the iPhone to make rapid calculations and alterations. The recipe here is a fluid object with experience used in making substitutions and adjustments. Our conclusions do not put forward ANT as an account for learning or a theory of learning. Rather we seek to illustrate the application and potential of ANTs sensibility in attending to the processes of socio-material practice. We also seek to extend the understanding of how learning can be seen in actor-network terms through providing evidence of learning’s transformative effects in the assemblage of a actor-network.